Peran Pustakawan dalam Penerapan Open Science di Perpustakaan Perguruan Tinggi - Yohanna Hariaty (Media Informasi, 2023)
Research as a way of producing Science or Science is a process that involves various activities. Every activity in the research process produces research data. Open science issues encourage libraries to make role changes. In the open science movement, university libraries are not limited to storing knowledge or science or using science for specific purposes. Still, they must be knowledge collaborators where knowledge generated from research can be accessed, critiqued, duplicated, and reproduced jointly and openly. This paper focuses on librarians' role in applying open science in university libraries using literature study methods. The analysis in this article is about essential libraries to consider how to prepare librarian functions to support the principles of transparency, conduct good data management, and understand research ethics. Librarians play an important role in implementing open science in college libraries as facilitators, research partners, and information managers who support the development of scientific knowledge. Librarians must innovate, create, and improve their ability to manage research data and provide practical support to researchers throughout the process to support transparent research and have a positive impact on universities.